Multiscalar investigation of FeVO4 conversion cathode for a low concentration Zn(CF3SO3)2 rechargeable Zn-ion aqueous battery - Kumar, Sonal (2021)
Battery cathode materials operating on multivalent‐ion intercalation are prone to short operational lifetimes, traditionally explained to be due to poor solid‐state diffusion. Here, we overcome this problem by using a conversion‐type cathode material and demonstrate the benefits in a FeVO4 host structure. The rechargeable Zn‐ion battery exhibits stability for an unprecedented operational lifetime of 57 days with a high capacity of 272 mAh g−1 (60 mA g−1) over 140 cycles. We use a combination of synchrotron‐based XAS, SRXTM, Raman, XRD and HRTEM techniques to elucidate the cathode material evolution at multilength‐scale for understanding the Zn‐ion storage mechanism. We further highlight the benefits of using a low‐salt concentration electrolyte and pH‐consideration analysis in aqueous battery development, the optimization of which leads to a 4‐fold increase in battery performance as compared to conventional high‐salt concentration electrolyte formulations.